Pengaruh Pendidikan dan Pengangguran terhadap Kemiskinan di Kota Jambi - Novi Wulandari; Nayla Desviona; Arieh Dwi Setia Putri; Dandy Pedrosa (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Urban poverty remains a complex development challenge in Indonesia, including in Jambi City. This study aims to examine the influence of education level and unemployment rate on the poverty level in Jambi City. A quantitative approach was employed using secondary cross-sectional data at the sub-district level for the year 2024 obtained from the Central Bureau of Statistics. The dependent variable is the poverty rate, while the independent variables consist of the open unemployment rate and education level, proxied by the percentage of the population with at least secondary education (senior high school or equivalent). Data were analyzed using multiple linear regression with the ordinary least squares (OLS) method. The results indicate that the unemployment rate has a positive and statistically significant effect on poverty in Jambi City. Meanwhile, the education variable shows a positive but statistically insignificant effect on poverty. These findings suggest that unemployment is a dominant factor influencing urban poverty, whereas improvements in education alone have not been sufficient to reduce poverty without adequate job creation. The study highlights the importance of integrating education policies with employment-oriented economic development strategies. The results are expected to provide empirical evidence to support local governments in formulating more effective and integrated poverty alleviation policies at the urban level.